2002
DOI: 10.1021/jp014353b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Potential Energy Surface of the C2H2FO Radical

Abstract: The potential energy surface of C2H2FO is investigated at CCSD(T)/6-311G(d,p)//B3LYP/6-311G(d,p) level. The results show that isomers of 1, 3, 4, 5, 5‘, 8, 9, and 9‘ are stable, and the energy barriers are more than 30 kcal/mol. Isomer 2 has, relatively speaking, much lower kinetic stability. The three cyclic isomers 6, 6‘, and 7 are less stable than the former, but more stable than the latter. The other isomers, such as isomers 1‘, 3‘, 4‘, 10, and 11 are less stable than isomer 2 in kinetics. Only isomer 1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…The frequencies presented in Table IV have been scaled by a factor of 0.9538 as recommended by Scott and Radom 42 for the QCISD/6-31G(d) level of theory. Additionally, the total ab initio energies are given in Table V at both the current level of theory and at the B3LYP/6-311G** and CCSD͑T͒/6-311G** levels as reported by Cao et al 7 Finally, the relative energies, including the zero-point vibrational energies ͑ZPVE͒ for the QCISD/6-311G** level, can be found in Table V and are illustrated in Fig. 9.…”
Section: B Ab Initio Calculationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The frequencies presented in Table IV have been scaled by a factor of 0.9538 as recommended by Scott and Radom 42 for the QCISD/6-31G(d) level of theory. Additionally, the total ab initio energies are given in Table V at both the current level of theory and at the B3LYP/6-311G** and CCSD͑T͒/6-311G** levels as reported by Cao et al 7 Finally, the relative energies, including the zero-point vibrational energies ͑ZPVE͒ for the QCISD/6-311G** level, can be found in Table V and are illustrated in Fig. 9.…”
Section: B Ab Initio Calculationsmentioning
confidence: 99%
“…The calculations of the ground state potential energy surface of C 2 H 2 FO by Cao et al 7 also do not include a dissociation pathway to this channel, although they reported a bimolecular transition state corresponding to FϩH 2 CCO→HFϩHCCO direct hydrogen abstraction.…”
Section: B Ab Initio Calculationsmentioning
confidence: 99%
See 3 more Smart Citations